Pre-IVF treatment with a GnRH antagonist in women with endometriosis (PREGNANT): study protocol for a prospective, double-blind, placebo-controlled trial - Hugh Taylor; Hao Huang; Lubna Pal; Heping Zhang; Howard J Li; Sandra Carson; Valerie Flores; Jared Robbins; Nanette F Santoro; James H Segars; David Seifer; Steven Young (BMJ Open)
Introduction Infertility is a common complication of endometriosis. While in vitro fertilisation-embryo transfer (IVF) successfully treats endometriosis-associated infertility, there is some evidence that pregnancy rates may be diminished in women seeing fertility treatment for endometriosis-associated infertility compared with other etiologies of infertility. The use of gonadotropin releasing hormone (GnRH) agonist prior to IVF has been suggested to improve success, however studies have been small and rarely reported live birth rates. Recent approval of an oral GnRH antagonist for endometriosis provides a novel option for women with endometriosis who are undergoing IVF. There have been no studies on the efficacy of GnRH antagonists for the treatment of endometriosis-related infertility.Methods and analysis This study is a multicentre, prospective, randomised, double-blind, placebo-controlled trial to study the efficacy of GnRH antagonist pretreatment for women with endometriosis who are undergoing IVF. A total of 814 patients with endometriosis undergoing fertility treatment will be enrolled and randomised 1:1 into two groups: elagolix 200 mg two times per day or placebo for 8 weeks, prior to undergoing IVF. All participants will then undergo IVF treatment per local protocols. The primary outcome is live birth. Secondary outcomes include oocyte number, fertilisation rate, embryo morphology and implantation rates, as well as rates of known endometriosis-related obstetrical outcomes (pregnancy-induced hypertension, antepartum haemorrhage, caesarean delivery and preterm birth).Ethics and dissemination The PREGnant trial was approved by the Institutional Review Board at Johns Hopkins University. Results will be published in a peer-reviewed journal.Trial registration number NCT04173169.